2.5k views
5 votes
-6x – 4y = -14

4x – 12y = -20

a. (1, 2)
b. (-2, 1)
c. (-2,4)
d. (-2,-4)

2 Answers

3 votes

Answer:

A.(1,2)

Explanation:

Step: Substitute

−2 /3 y + 7 /3

4x−12y=−20:

4x−12y=−20

4( −2 /3 y + 7 /3 )−12y=−20

-44/3y + 28 /3 =−20(Simplify both sides of the equation)

−44 /3 y + 28 /3 + −28 /3 =−20+ −28 /3

(Add (-28)/3 to both sides)

−44 /3 y= −88 /3

−44 /3 y

−44 /3 = −88 /3 −44 /3

(Divide both sides by (-44)/3)

y=2

Step: Substitute2foryinx=

−2 /3 y+ 7 /3 :

x= −2 /3 y+ 7 /3

x= −2 /3 (2)+ 7 /3

x=1(Simplify both sides of the equation)

Answer:

x=1 and y=2

User Tyler Replogle
by
6.3k points
2 votes
It’s probably A. (1,2) hope this helps..
User Sampat
by
5.9k points